Formulation of novel DFMA rules for the advancement of ergonomic factors in non-linear iterative prototype assembly. Issue 8 (3rd August 2018) - Matthews, Sami; Leminen, Ville; Eskelinen, Harri; Toghyani, Amir; Varis, Juha
ABSTRACT: The Design for Manufacturing and Assembly (DFMA) is usually associated with mass production. Iterative prototype construction and assembly have not been taken into account commonly in the planning of assembly ergonomics. This article presents DFMA queries considering factors in geometry and construction that affect the adjustability and adaptability during prototype construction. The example case concerns a paperboard tray press-forming prototype line. The main observation is that a DFMA approach with a systematic ergonomics analysis supports the efforts to avoid unnecessary reassembly cycles of the design. It was found in the study that although the total number of parts was increased, the reassembly times and the number of injuries were reduced significantly. The DFMA rules generated in this article can be applied in any non-linear prototype construction to enable a more clarified and safer operating environment.